2003
DOI: 10.18084/1084-7219.8.2.147
|View full text |Cite
|
Sign up to set email alerts
|

People First: A Case Study in Partnering with the Community

Abstract: This case study demonstrates the process by which a class composed of senior social work students learns macro practice values and skills by partnering with a community organization. The products of this collaboration emerge from the real-life problem scenario in which students, community partners, and the social work educator collaborate to develop the skills necessary to resolve problems. Through community partnership, social work educators are in the position to expand the opportunities for students to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Where reports claim that partnership learning benefits students, they do so mainly in terms of students’ attitudes and understandings, indicative of fitness to practice, rather than demonstrable practice itself. The exception is Bordelon (2003), who considered that his students and community group partners achieved effective service plans far exceeding expectations. Few studies though are sufficiently outcome‐focused to judge whether partnership education made a difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where reports claim that partnership learning benefits students, they do so mainly in terms of students’ attitudes and understandings, indicative of fitness to practice, rather than demonstrable practice itself. The exception is Bordelon (2003), who considered that his students and community group partners achieved effective service plans far exceeding expectations. Few studies though are sufficiently outcome‐focused to judge whether partnership education made a difference.…”
Section: Resultsmentioning
confidence: 99%
“…Where claims are made that the benefits of partnership learning are demonstrated in practice, it is largely in terms of skills in listening, showing empathy and respect, and recognising the strengths and wisdom which users bring to the relationship (Bordelon 2003, Scheyett & Kim 2004). Wikler (1979) concluded that the most important skill enhanced by partnership learning was ‘really listening’ (Wikler 1979, p. 149).…”
Section: Resultsmentioning
confidence: 99%
“…One identified approach requires students to engage in an in-depth community study or needs assessment within the context of a macro practice class (Hymans, 2000;Sherraden, 1993). Bordelon (2003) describes a practice class in which students create a universitycommunity partnership along with their instructor, and Huber and Orlando (1993) define an innovation that engages students in an in-class, hypothetical project to challenge the bounds of their interventive thinking. Other approaches invite students to engage in advocacy (Butler & Coleman, 1997;Raber & Richter, 1999), and still further approaches are designed to address the nature of field placements, field assignments and field instruction (Allen & Shragge, 1995;Kasper & Wiegand, 1999;Koerin et al, 2000;Siu, 1991;Skolink & Papell, 1994;Wolk, Pray, Weismiller, & Dempsey, 1996).…”
Section: Macro Practicementioning
confidence: 99%